Barriers and facilitators to primary health care for people with intellectual disabilities and/or autism: an integrative review - Alison Jayne Doherty; Helen Atherton; Paul Boland; Richard Hastings; Lucy Hives; Kerry Hood; Lynn James-Jenkinson; Ralph Leavey; Elizabeth Randell; Janet Reed; Laurence Taggart; Neil Wilson; et al. (BJGP Open, 2020)
Background: Globally, people with intellectual disabilities and/or autism experience health inequalities. Death occurs at a younger age and the prevalence of long-term morbidities is higher than in the general population. Despite this, their primary healthcare access rates are lower than the general population, their health needs are often unmet, and their views and experiences are frequently overlooked in research, policy, and practice. Aim: To investigate the barriers and facilitators reported by individuals with intellectual disabilities, autism, or both, and/or their carers, to accessing and utilising primary health care for their physical and mental health needs. Design & setting: An integrative review was undertaken, which used systematic review methodology. Method: Electronic databases MEDLINE, Embase, CINAHL (Cumulative Index to Nursing and Allied Health Literature), and Cochrane were searched for relevant studies (all languages) using a search strategy. Two researchers independently screened the results and assessed the quality of the studies. Results: Sixty-three international studies were identified. Six main themes relating to barriers and facilitators emerged from an analysis of these studies. The main themes were: training; knowledge and awareness; communication; fear and embarrassment; involvement in healthcare decision-making; and time. All the themes were underpinned by the need for greater care, dignity, respect, collaborative relationships, and reasonable adjustments. Opposing barriers and facilitators were identified within each of the main themes. Conclusion: Adolescents and adults with intellectual disabilities and/or autism experience several barriers to accessing and utilising primary health care. The findings highlight the reasonable adjustments and facilitators that can be implemented to ensure that these individuals are not excluded from primary health care.